Investigating the Relations between Social Influence, User’s Attitudes and Behavioural Intention in a Persuasive Website Environment - Ibrahim, Nurulhuda; Fairuz Shiratuddin, Mohd; Wai Wong, Kok (International Journal of Engineering and Technology, 2018)
In an online environment, visual design plays an important role in influencing web users' impression of a website. Previous research has clarified that different elements of visual design stir up dissimilar impacts towards the end-users. This paper investigates the impact of persuasive visual towards users' attitudes and behaviours. Specifically, it examines the critical roles of social influence in the form of visual persuasion in motivating users to have a favourable impression of a particular website. Survey data was collected in an experimental study that was conducted online. Structural model assessment is carried out using confirmatory factor analysis (CFA) in conjunction with PLS-SEM analyses. The general analysis of model fit indicates that the two models proposed in this paper surpassed the cut off values for model acceptance with most of the model fit criteria reflects outstanding explanatory power. The findings offer new insights into the role of visual persuasion in web design with respect to the relationships between social influence, users' attitudes, and intentional behaviour.Â Â